Optimization Machine Maintenance Model With Consider Repair Costs and Number of Repairman at PT. SNP - Murwan Widyantoro; Yuri Delano Regent Montororing; Apriyani Apriyani (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2022)
To expedite the production process, companies need to make adjustments to technological developments to support company performance. This is done so that the company does not experience problems in the production process. One of the technologies used in manufacturing companies is a machine that can simplify the production process so that companies can optimize time and energy. The machine used must be guaranteed to operate at high performance, so periodic inspections must be carried out. In machine maintenance activities at PT. SNP, not based on damage data as a reference, and in its implementation is still not programmed. In this study, a solution will be sought to overcome the problem of optimal machine scheduling by considering the cost of repairs and number of repairman. The historical data of engine failure will be used to calculate the Mean Time Between Failure (MTBF) and Mean Time to Repair (MTTR) and model the engine maintenance, so that it is expected to be able to reduce repair costs.